Pancasila as The Basis Of Constitutional Law: Shaping Legal Principles and Jurisprudence - Harianti, Isnin; Amri, Ahmad Ihsan; Muthar, Achmad; Rato, Dominikus; Basarah, Ahmad (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
This research aims to explore the role of Pancasila as the legal basis of the constitution and its influence in shaping legal principles and jurisprudence in Indonesia. Using the document analysis method, this research examines legal documents, including the constitution, laws, and court decisions, to understand how Pancasila values are integrated into national law. John Locke's theory of natural rights and social contract is applied as a theoretical framework to dissect and assess the role of Pancasila in the context of constitutional law. The research finds that Pancasila, with its universal principles, serves as a strong foundation for building a democratic and just legal system, which is in line with Locke's views on limited government and the protection of individual rights.